Long-term outcomes of the recovery approach in a high-security mental health setting: a 20 year follow-up study - Thomson, Lindsay; Rees, Cheryl (Frontiers in Psychiatry, 2023)
Background: This study examines outcomes from a descriptive longitudinal cohort of 241 patients first explored in a whole population study of the high secure State Hospital for Scotland and Northern Ireland during 1992/93. Partial follow up of patients with schizophrenia was conducted during 2000/01 with 20 year follow up initiated during 2014. Aims: To explore what happens to patients who required high secure care during a 20 year follow up period. Method: Previously collected data have been amalgamated with newly collected information to examine recovery journey since baseline. A diversity of sources were employed including patient and keyworker interview, case note review and extraction from health, national records and Police Scotland datasets. Results: Over half the cohort (56.0%), where data were available, resided out with secure services at some point during follow up (mean 19.2 years), with only 12% unable to transition from high secure care. Symptoms of psychosis improved with statistically significant reductions observed for reported delusions, depression and flattened affect. Reported sadness (MADRS) at baseline, first and 20 year follow up interview were negatively correlated with QPR recovery scores at 20 year follow up although qualitative data presented a picture of progress and personal development. There was little evidence of sustained social or functional recovery with reference to societal measures. The overall conviction rate post baseline was 22.7% with 7.9% violent recidivism. In general, the cohort evidenced poor morbidity and mortality with 36.9% of the cohort dying, primarily of natural causes (91%). Conclusions: Overall, findings are positive for movement on from high security, symptom improvement and low levels of recidivism. The high rate of deaths observed among this cohort and poor physical morbidity were notable, along with a lack of sustained social recovery particularly among those who had negotiated a path through services and who were now resident in the community. Social engagement, enhanced during residence in low/open services, was greatly curtailed on transition to the community. This is likely a reflection of self-protective measures adopted to mitigate societal stigma as well as removal from a communal setting. Subjective depressive symptoms may impact upon wider aspects of recovery.